Pengaruh Net Profit Margin dan Current Ratio Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan Manufaktur Sub Sektor Plastik dan Logam - Maf’ul Nadhifah (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This study aims to examine the effect of Net Profit Margin (NPM) and Current Ratio on disclosure of corporate social responsibility (CSR). Net Profit Margin (NPM) is used by companies to determine the company's ability to achieve profits by comparing net income with sales volume. Current Ratio is used to measure a company's ability to pay its obligations. This study used 95 populations and samples from the manufacturing companies of the plastic and packaging sub-sectors listed on the Indonesia Stock Exchange as many as 75 for the period 2012-2016, with a purposive sampling method. The results of the study show that: (1) Net Profit Margin has no effect on CSR disclosure, not all companies that get high profit rates will allocate funds for corporate social responsibility programs because the profits generated will be reprocessed through asset development. (2) Current Ratio does not affect CSR disclosure.